Virulence and Antimicrobial-Resistant Gene Profiles of Salmonella spp. Isolates from Chicken Carcasses Markets in Ibague City, Colombia - Kelly Johanna Lozano-Villegas; Iang Schroniltgen Rondón-Barragán (International Journal of Microbiology)
Salmonella spp. is one of the leading causes of foodborne bacterial infections, with major impacts on public health and healthcare system. Salmonella is commonly transmitted via the fecal-to-oral route, and food contaminated with the bacteria (e.g., poultry products) is considered a common source of infection, being a potential risk for public health. The study aims to characterize the antimicrobial resistance- and virulence-associated genes in Salmonella isolates recovered from chicken marketed carcasses (n = 20). The presence of 14 antimicrobial and 23 virulence genes was evaluated using end-point PCR. The antimicrobial genes were detected in the following proportion among the isolates: blaTEM 100%, dfrA1 and blaCMY2 90% (n = 18), aadA1 75% (n = 15), sul1 and sul2 50% (n = 10), floR 45% (n = 9), qnrD 20% (n = 4), and aadA2 15% (n = 3). catA, sul3, qnrS, and aac(6′)-Ib genes were absent in all isolates. Regarding virulence-associated genes, all Salmonella strains contain invA, fimA, avrA, msgA, sopB, and sopE. The cdtB gene was present in 95% (n = 19) of isolates, whereas spvC and spvB were present in 55% (n = 11). Other virulence genes such as spiC, lpfC, lpfA, and csgA were present in 90% (n = 18) of strains. The presence of antimicrobial and virulence genes in several Salmonella strains in chicken meat suggests the potential pathogenicity of the strains, which is relevant given the possibility of cross-contamination which represents a significant threat to public health.